2018
DOI: 10.3390/brainsci8040051
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Trick in a Patient with Cervical Dystonia: Insights from Magnetoencephalography

Abstract: Background: The proposed mechanisms for the sensory trick include peripheral sensory feedback to aid in correcting abnormal posture or movement. Case report: A 53-year-old woman with cervical dystonia underwent magnetoencephalography pre- and post-botulinum toxin injection and sensory trick, which was described as yawning. Study revealed connectivity between the left frontal and inferior frontal gyrus before yawning, which changed to the visual cortex and right middle frontal gyrus with yawning. Beta frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Magnetoencephalography coherence source imaging (MEG-CSI) has also been used to investigate CD [ 9 , 10 ]. Our previous MEG-CSI study demonstrated difference in resting-state coherence between controls and CD patients in the fronto-striatal region, but not in occipito-striatal, parieto-striatal and striato-temporal networks [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoencephalography coherence source imaging (MEG-CSI) has also been used to investigate CD [ 9 , 10 ]. Our previous MEG-CSI study demonstrated difference in resting-state coherence between controls and CD patients in the fronto-striatal region, but not in occipito-striatal, parieto-striatal and striato-temporal networks [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 This is further supported by a recent case study demonstrating an association between the effect of sensory trick and physiological characteristics of the parietal cortex, which is known for its role in sensorimotor integration. 11 Perhaps gradually decreasing plasticity in the sensorimotor mappings, in a manner specific to CD pathology and not just age-related, makes the sensory trick less effective over time.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the following MEG-based MEG-CSI methodology and data processing used in this study has been previously published by our lab. 10,11…”
Section: Methodsmentioning
confidence: 99%
“…9 Our lab has also previously published work on cervical dystonia using MEG-CSI. 10,11 In the present study, we characterized the functional connectivity in a patient with ED where touch is used to evoke dystonic movements.…”
Section: Introductionmentioning
confidence: 99%